“Prueba regional de veinte variedades promisorias de soya (glycine max (L) merril) en el huallaga central -departamento San Martín” - Díaz Reátegui, Jorge Wilson (2004)
This Present work was accomplished between April/ August, months, year 2003 on a loamy clay texture, vertisol soil; 7.5 pH, 4.4% organic matter, 17 ppm available phosphorus, 0.67 Cmol(+)kg exchangeable potassium and 26 Cmol(+) Kg exchangeable Calcium + Magnesium on grounds belonging to the national university of San Martin, Picota province, caspizapa district San Martin departament. The aim of this survey was to evaluate both the botanical and agronomical characteristics in twenty soybean varieties in central huallaga. We used a randomized block design to include twenty treatments and three repetitions. The soybean varieties evaluated were from brazil. Results determined that the following varieties gave the best yielding: V26 (6107.90 Kg/ha.), V11 (5460.50 kg/ha.), V34 (5044.40), V19 (4892.00Kg/ha.), V33 (4838.00), V23 (4428.50), V31 (4412.70}, V20 4126.90) and V1s (4066.60) kg/ha. respectively. Showing the total production a positive benefit/cost relateon. Also varietaly V54 was most precacions to beginning of the flowering and maturing with 25.3 and 90.0 days respectively. As for as the varietaly that obtained the greater pod height next soil was V26 with 17.03 centimetres, also tosay the number of pods by plant, varietaly V24 was winner with 416.0, also the varietaly that had weightest of a hundred seeds was the varietaly V54 with 30 gr. As well.